The Effect Of Using Audio Visual Media On The Speaking Skills Of Students At SD Negeri 11 Leang-Leang Bantimurung District Kabupaten Maros - Titin Nurjayanti; Widya Karmilasari Achmad; Nurfaizah AP (Program Studi PGSD FIP UNM, 2021)
This research is a research that uses a quantitative approach with the type ofexperimental research which aims to find out (1) The description of the use of audio-visualmediaonthespeakingskillsofthirdgradestudentsofSDNegeri11Leang-Leang,Bantimurung District, Maros Regency, (2) The description of students' speaking skills afterusing audio-visual media in class III SD Negeri 11 Leang-Leang, Bantimurung District,MarosRegency,(3)Theeffectofthe useofaudio-visual media on the speaking skills of grade III students of SD Negeri 11 Leang-Leang, Bantimurung District, Maros Regency. Theindependent variable in this study is the use of audio-visual media, while the dependentvariable is the result of students' speaking skills. This study uses the type of research OneGroup Pretest-Posttest Design. The population in this study were 23 students of class III SDNegeri 11 Leang-Leang, Bantimurung District, Maros Regency in the academic year 2020-2021. Determination of the sample in this study using non-probability sampling, purposive sampling. Data collection techniques in research are tests, observation and documentation. Data were collected from giving speaking skills test and the analyzed by descriptive statistics and inferential statistics using the paired sample T-Test with the help of SPSS22.0calculations.The results of the research that have been carried out, it can becon cluded that: (1) The description of the use of audio-visual media on students' speaking skills is seen basedon the observation sheet, from the learning stages observed at each meeting the learningprocess seems to increase through the activities of students and teachers, (2) The descriptionof the results of students' speaking skills after using audio-visual media is more improved.Thisis evidenced by the posttest averages core of students in the very good category whilethe pretest scores are in the poor category, (3) There is a significant effect of the use of audio-visual media on students' speaking skills. This is because the probability value oftcount > ttable(55.631> 2.074), with a significance value of 0.000 is smaller than the significance level of0.05 (0.000 <0.05).